The Influence of Social Media Fatigue on Consumer Behavior of TikTok Users Active in Jakarta - Nareswari Paramesti; Renny Risqiani; Rashieka Ghinaa R; Dylan Rachmat Riyanta; Arkaan Athooya Hadi; Dhaniki Purnomo (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
This study aims to analyze the influence of Branded Content Overload, Branded Content Irrelevance, and Branded Ads Intrusiveness on Social Media Fatigue, as well as its impact on Lurking Behavior among TikTok users in Jakarta. This research employs a quantitative method with a survey approach using questionnaires distributed to respondents. Data was collected from 250 active TikTok users in Jakarta. The results reveal that Branded Content Overload, Branded Content Irrelevance, and Branded Ads Intrusiveness positively affect Social Media Fatigue. Furthermore, Social Media Fatigue significantly drives passive user behavior, known as Lurking Behavior. Mediation analysis indicates that Social Media Fatigue mediates the relationship between independent variables and Lurking Behavior. These findings provide practical implications for marketers to regulate content frequency, relevance, and intrusiveness to avoid user fatigue and maintain engagement on social media platforms.